Faktor Spesifik Bank, Inflasi, dan Profitabilitas Bank Go Public (Studi Empiris pada Negara Asean-5) - Siska Marista Putri; Harjum Muharam (Diponegoro Journal of Management, 2025)
This study examines the influence of bank-specific factors and inflation on the profitability of go public banks in ASEAN-5 countries, namely Indonesia, Malaysia, Singapore, Thailand, and the Philippines in 2019-2023. EAR, liquidity (LDR), credit risk (NPL), and bank size are indicators of bank-specific factors. Bank profitability is measured by Return on Assets (ROA).The data in this study were obtained from Bloomberg Terminal, the annual reports of each bank, and the World Bank. The population used was 95 go public banks in 2019-2023. The sampling technique used was the purposive sampling method and a research sample of 75 banks was obtained. The research data were analyzed using the panel data regression method, namely a combination of cross-section and time series with Random Effect as the selected model. The tests used consisted of the classical assumption test, F test, t-test, and determination coefficient test.The result of the study indicates that EAR, bank size, and inflation have a positive and significant effect on profitability (ROA), while liquidity (LDR), and credit risk (NPL) do not have a significant effect on bank profitability (ROA).